PROMOTION OF SELF-CARE FOR MASTECTOMIZED WOMEN - Aline Priscila Rego de Carvalho; Taciana Mirella Batista dos Santos; Francisca Márcia Pereira Linhares (Universidade Federal do Paraná, 2012)
This descriptive, exploratory study aimed to devise a nursing care plan for women who had undergone mastectomy, in the promotion of self-care, based on analysis of the discourses of those who had received the surgery between January and August 2009. The research was grounded in Orem's Theory, which guides nursing care at any stage of the patient's life, whether in maintenance of well-being, recuperation of health, prevention of illness or rehabilitation. The following themes emerged from the discourses: Educative actions centered on self-care, Care centered on the needs of mastectomized women and in active listening involving the network of social support, and Group meetings: a facilitative strategy for personal coping. These permeate the guidance and the way of providing it for promoting self-care in the post-operative phase. In the study, the authors perceived the limitations on the women's knowledge about the care to be taken in the peri-operative period